COVID-19 and Personality: A Cross-Sectional Multicenter Study of the Relationship Between Personality Factors and COVID-19-Related Impacts, Concerns, and Behaviors - AL-Omiri, Mahmoud K.; Alzoubi, Ibrahim A.; Al Nazeh, Abdullah A.; Alomiri, Abdallah K.; Maswady, Mohannad N.; Lynch, Edward (Frontiers in Psychiatry, 2021)
Background: This cross-sectional observational study aimed to evaluate coronavirus disease 2019 (COVID-19)-related precautions to avoid COVID-19 infection, distress and behavioral changes, fears and concerns, and effects on opinions and beliefs among participants from different backgrounds and also to identify the relationships between personality factors and COVID-19-related changes and impacts. Methods: One thousand and three hundred nineteen participants (744 females and 575 males, mean age ± SD = 32.7 ± 11.6 years) completed a three-section survey collecting data regarding demographic information, personality factors [using the NEO Five-Factor Inventory (NEO-FFI)], and COVID-19-related issues (using the VAS scale). Findings: COVID-19 was associated with changes related to precautions to avoid COVID-19 infection, distress and behavioral changes, fears and concerns, and effects on opinions and beliefs (P < 0.05). Higher neuroticism scores were associated with more negative COVID-19-related changes and impacts (P < 0.05). Higher extraversion, agreeableness, and conscientiousness scores were associated with more acceptance of COVID-19 containment measures as well as less COVID-19-related changes and impacts (P < 0.05). Conclusions: Personality factors were associated with COVID-19-related impacts. These findings demonstrate the importance of the relationship between personality factors and COVID-19-related changes.